A Descriptive Study: Evaluation of Delayed Laboratory Testing in Emergency Room - Kurniawan, Linny Luciana; Dyah Indrasari, Nuri; Solin, Ro Shinta Christina (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Precision, accuracy, and short turnaround time (TAT) are important to improve the quality and effectiveness of laboratory services in the Emergency Room (ER). Several studies reported an average of 60% the ratio of anticoagulant to sample is not appropriate, lysis, and clotted samples occurred in the pre-analytical part. This part consisted of the request/registration of laboratory tests, patient preparation, specimen collection, and transportation to the central laboratory. The aim of this research is to evaluate the cause of the long TAT for laboratory research so as to obtain problem solving based on the target. This observational study was conducted in 2021 at the ER laboratory outlet. Observations were made started from the workload carried out by the laboratory technician, sample registration, and data collection from the Laboratory Information System (LIS). The study obtained 14.709 samples from the LIS at the Clinical Pathology Department, Cipto Mangunkusumo Hospital. The highest sample rejection rate was from the ER laboratory outlet due to specimen lysis (2.79%). The average time required for re-collecting specimens was around 2-2.5 hours. This rejection was below the minimum quality standards based on the International Federation of Clinical Chemistry (IFCC). Other problems include the limited number of medical laboratory experts compared to the workload also inefficient Computerized Physician Order Entry (CPOE) registration methods. The main problem of delayed laboratory testing in the emergency department is the pre-analytical part including sample registration and rejection specimens. That rejection mostly comes from lysis specimens, which caused invalid laboratory result.